2016
DOI: 10.21608/eijest.2013.96783
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Concrete Gravity Dams

Abstract: Dams and reservoirs located near populated areas represent a potential risk in the event of uncontrolled release of the reservoir water due to earthquake damage, endangering the people and properties. In the present work, the seismic performance of concrete gravity dams is studied numerically using commercially Finite Element based software ADINA (Automatic Dynamic Incremental Nonlinear Analysis). The study gives deep insight into the procedure of analysis and safety evaluation of concrete gravity dams, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…Since the dam portion would have been at a height to induce tensile damage near the crest of the gravity dam, Zappitelli et al [10,39] found that displacement quantity was a major impact for gravity dams with a greater downstream slope. The elevation of the gravity dam had an impact on the horizontal displacement of the gravity dam top, according to Zappitelli et al [10,32,54,55]. The gravity dams with the greatest displacement value at the maximum height were the most resistant to bottom limitations, which was because the upper section of the dam was subjected to a bigger impact.…”
Section: Displacement For Gravity Dammentioning
confidence: 99%
See 4 more Smart Citations
“…Since the dam portion would have been at a height to induce tensile damage near the crest of the gravity dam, Zappitelli et al [10,39] found that displacement quantity was a major impact for gravity dams with a greater downstream slope. The elevation of the gravity dam had an impact on the horizontal displacement of the gravity dam top, according to Zappitelli et al [10,32,54,55]. The gravity dams with the greatest displacement value at the maximum height were the most resistant to bottom limitations, which was because the upper section of the dam was subjected to a bigger impact.…”
Section: Displacement For Gravity Dammentioning
confidence: 99%
“…The researcher showed that raising the magnitude of the earthquake had a 0.04 percent variation in the settling of the gravity dam's body from its stable condition for PGA= 0.1g and elevation of the water/height of the dam (hw/h) =0.25. As the height of the gravity dam was increased to (hw/ h)=0.95, there was a 0.16 percent rise in the quantity of settling [55].…”
Section: Displacement For Gravity Dammentioning
confidence: 99%
See 3 more Smart Citations